USM EXPLORES COLLABORATION WITH NRIAG EGYPT IN GEOPHYSICS AND ASTRONOMY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 13 May 2016 – Universiti Sains Malaysia (USM) intends to explore and further develops the study in geophysics and astronomy through a collaboration between the USM School of Physics and the National Research Institute of Astronomy and Geophysics (NRIAG), Egypt.